تفعيل دور الجباية العادية في الجزائر - أوضايفية، حدة (جامعة عباس لغرور خنشلة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2022)
تلعب الجباية العادية دورا استراتيجيا في الكثير من اقتصاديات الدول كأحدة أهم مصادر الدخل، وهذا ما يغيب بالنسبة للاقتصاد الجزائري الذي يظل تمويل التنمية الاقتصادية فيه خاضعا لتقلبات الإيرادات النفطية المرتبطة هي الأخرى بعوامل خارجية يصعب التحكم فيها، هذا ما ستحاول هذه الورقة البحثية إلقاء الضوء عليه من خلال واقع الجباية العادية في الجزائر خاصة مع تراجع إيرادات الجباية البترولية نتيجة انخفاض أسعار النفط، وأهم العراقيل التي يوجهها تعبئة مثل هذه الموارد الضريبية. وقد كشفت الدراسة أن الجباية العادية في الجزائر تعاني من عدة عراقيل تجعل مساهمتها ضعيفة في تمويل الاقتصاد نتيجة غياب استراتيجية واعية تساهم في تنويع مصادر الدخل والتمويل خارج الريع النفطي. مما يفرض ضرورة تفعيل الإصلاحات في هذا الجانب. Ordinary taxation plays a strategic role in many countries’ economies as one of the most important sources of income, and this is what is absent for the Algerian economy, in which the financing of economic development remains subject to fluctuations in oil revenues, which are also linked to external factors that are difficult to control. This is what this research paper will attempt to shed light on. Through the reality of regular taxation in Algeria, especially with the decline in petroleum tax revenues as a result of low oil prices, and the most important obstacles faced by the mobilization of such tax resources. The study revealed that the normal collection in Algeria suffers from several obstacles that make its contribution weak in financing the economy as a result of the absence of a conscious strategy that contributes to diversifying sources of income and financing outside of oil rents. Which imposes the need to activate reforms in this aspect.
Keywords: الاقتصاد الجزائري -- التنمية الاقتصادية -- الموارد الضريبية -- التمويل النفطي -- الجباية البترولية -- أسواق النفط